Entre Téhéran et Dubaï, la naissance d’un marché de l’art « régional » entre 2005 et 2010 - Alexandre Kazerouni (Bulletin de l’Association de Géographes Français)
Dubai has become the centre of a « regional » art market between 2005 and 2010 thanks to the setting of a local network of galeries, auction sales by Christie’s and an art fair named Art Dubai. A historical and microsociological study of those three fundamental pillars reveals the role played by Iran as a main source of artworks, artists, art dealers and collectors in the birth of this art market, and connects this dynamics that has a cultural face to the already existing flows of immigrants and traded commodities between the two shores of the Persian Gulf since the Iranian revolution of 1979